Adjustment of azathioprine dose should be based on a lower 6-TGN target level to avoid leucopenia in NUDT15 intermediate metabolisers - Kang, Ben; Kim, Tae Jun; Choi, Jaeyoung; Baek, Sun Young; Ahn, Soohyun; Choi, Rihwa; Lee, Soo Youn; Choe, Yon Ho (Alimentary Pharmacology and Therapeutics, 2020)
Background: The association between NUDT15 polymorphisms and thiopurine-induced leucopenia is well known. Aim: To investigate the association between NUDT15 polymorphisms and time-to-leucopenia in paediatric patients with inflammatory bowel disease (IBD) receiving azathioprine and to determine the relationship between NUDT15 polymorphisms and 6-thioguanine nucleotide (6-TGN) levels. Methods: This retrospective observational study included Korean paediatric patients with IBD who were treated with azathioprine and underwent NUDT15 and TPMT genotyping. Azathioprine doses were adjusted by regular thiopurine metabolite monitoring. Factors associated with time-to-leucopenia and the relationship between NUDT15 polymorphisms and 6-TGN levels were analysed. Results: Among the 167 patients included, leucopenia was observed in 16% (19/119), 44% (20/45) and 100% (3/3) of the NUDT15 normal, intermediate and poor metabolisers respectively (P < 0.001). NUDT15 polymorphism was significantly associated with time-to-leucopenia (HR = 5.26, 95% CI = 2.74-10.09, P < 0.001). There was a positive association between 6-TGN levels and leucopenia among the NUDT15 intermediate/TPMT normal metabolisers (median 361.3 vs 263.8 pmol/8 × 108 RBC, P = 0.013). The most accurate 6-TGN cut-off level associated with leucopenia was 308.2 pmol/8 × 108 RBC (AUC = 0.742, 95% CI = 0.569-0.915, sensitivity 80.0%, specificity 72.7%, P < 0.001) in this subgroup. When the specificity was set to <15%, the 6-TGN cut-off level was 167.1 pmol/8 × 108 RBC (sensitivity 93.3%, specificity 13.6%). Conclusions: NUDT15 polymorphisms were associated with time-to-leucopenia during azathioprine treatment in Korean paediatric patients with IBD. In order to reduce the development of thiopurine-induced leucopenia (<15%) in NUDT15 intermediate metabolisers, adjustment of azathioprine doses should be based on a lower 6-TGN target level (<167.1 pmol/8 × 108 RBC).
Keywords: Adolescent; Azathioprine; Child; Female; Guanine Nucleotides; Humans; Immunosuppressive Agents; Inflammatory Bowel Diseases; Leukopenia; Male; Methyltransferases; Polymorphism, Genetic; Pyrophosphatases; Thionucleotides